2017
DOI: 10.1038/srep44285
|View full text |Cite
|
Sign up to set email alerts
|

Pitch discrimination associated with phonological awareness: Evidence from congenital amusia

Abstract: Research suggests that musical skills are associated with phonological abilities. To further investigate this association, we examined whether phonological impairments are evident in individuals with poor music abilities. Twenty individuals with congenital amusia and 20 matched controls were assessed on a pure-tone pitch discrimination task, a rhythm discrimination task, and four phonological tests. Amusic participants showed deficits in discriminating pitch and discriminating rhythmic patterns that involve a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
2
13
1
Order By: Relevance
“…Still, we can notice that the cases of comorbidity scored among the lowest in the phonological awareness/RAN component (eight cases out of 13 under the − 1.5 threshold). This observation had already been made by Couvignou et al (2019) in their adult study and is consistent with the results of previous works reporting weak phonological awareness in a significant proportion of amusic individuals (Jones et al, 2009;Sun et al, 2017). As argued in the introduction, both amusia and dyslexia can be conceptualized as disorders of conscious access to mental representations (Loui et al, 2011;Peretz et al, 2009;Ramus and Ahissar, 2012).…”
Section: Explanatory Hypothesessupporting
confidence: 89%
See 1 more Smart Citation
“…Still, we can notice that the cases of comorbidity scored among the lowest in the phonological awareness/RAN component (eight cases out of 13 under the − 1.5 threshold). This observation had already been made by Couvignou et al (2019) in their adult study and is consistent with the results of previous works reporting weak phonological awareness in a significant proportion of amusic individuals (Jones et al, 2009;Sun et al, 2017). As argued in the introduction, both amusia and dyslexia can be conceptualized as disorders of conscious access to mental representations (Loui et al, 2011;Peretz et al, 2009;Ramus and Ahissar, 2012).…”
Section: Explanatory Hypothesessupporting
confidence: 89%
“…Conversely, fine speech processing difficulties have been reported in amusia: although amusic individuals have a normal understanding of speech and prosody in everyday life (Ayotte et al, 2002), their pitch-processing deficit might extend to subtle deficits in processing speech intonation (Hutchins et al, 2010;Liu et al, 2010;Patel et al, 2008) and emotional prosody (Lolli et al, 2015;Pralus et al, 2019) as well as processing pitch contrasts in tone language words (Liu et al, 2016;Nan et al, 2010;Tang et al, 2018;Tillmann et al, 2011;Zhang et al, 2017). Besides, a few studies reported phonological awareness impairments in a subset of amusic individuals (Jones et al, 2009;Sun et al, 2017). More generally, several empirical studies show correlations between pitch perception skills and reading level, both in typically developing children (Anvari et al, 2002;Loui et al, 2011) and in children with reading difficulties (Cogo-Moreira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, amusic participants were identified using a screening method based on the three pitch-related subtests (Scale, Contour and Interval) from the Montreal Battery of Evaluation of Amusia (MBEA; Peretz et al, 2003 ) with an aggregate accuracy rate of 72.22% being the cutoff (i.e., 65 out of 90 points; Liu et al, 2010 ; Sun et al, 2017 ; Thompson et al, 2012 ). The ability to detect changes in melodic pitch, assessed by the three subtests that we employed, is fundamental to the processing melodic syntax, which was the focus of our investigation.…”
Section: Methodsmentioning
confidence: 99%
“…They also had normal hearing (<30 dB) in both ears at the frequencies of 0.25, 0.5, 1, 2, 4, and 8 kHz, which was confirmed using an Otovation Amplitude T3 series audiometer (Otovation LLC, PA, United States). Individuals with dyslexia were excluded from the investigation, and previous research confirms that amusic and control participants have similar general linguistic skills ( Sun et al, 2017 ). No participant reported neurological or psychiatric disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Along the same line, our recent behavioral studies showed that, compared with controls, people with congenital amusia perform worse on spatial representation and mental rotation task [25]. Similar studies also suggested that pitch processing may rely on cognitive mechanisms that are similar to those used for spatial processing [26,27], although, some other researchers failed to find an association between congenital amusia and deficits in spatial processing [28,29]. To date, investigations into whether congenital amusics have other kinds of non-musical deficiencies have been limited to the examination of language ability and spatial ability.…”
Section: Introductionmentioning
confidence: 82%